(+)‐Catechin ameliorates diabetic nephropathy by trapping methylglyoxal in type 2 diabetic mice. Issue 12 (27th October 2014) - Zhu, Dina; Wang, Lei; Zhou, Qile; Yan, Shijun; Li, Zhi; Sheng, Jun; Zhang, Wensheng
<x xml:space="preserve">Abstract</x> Scope Accumulation of glycolytic metabolite methylglyoxal (MG) in diabetic kidney is thought to contribute to the pathogenesis of nephropathy, either as a direct toxin or as a precursor for advanced glycation end products (AGEs). Using (+)‐catechin (CE), a novel MG trapper, we investigated whether MG trapping is sufficient to prevent the progression of diabetic nephropathy in type 2 diabetic mice. Methods and results CE markedly trapped exogenous MG in a time‐ and dose‐dependent manner and formed mono‐MG‐CE and di‐MG‐CE adducts, which were characterized by HPLC‐ESI‐Q‐TOFMS. In vivo, CE administration for 16 wk significantly ameliorated renal dysfunction in type 2 diabetic db/db mice, partially due to MG trapping, which in turn inhibited AGEs formation and lowered proinflammatory cytokines, including tumor necrosis factor α and IL‐1β. Similarly, the MG trapping and cellular signaling inhibition effects of CE were observed in human endothelium‐derived cells under high glucose conditions. Conclusion CE might ameliorate renal dysfunction in diabetic mice as consequences of inhibiting AGEs formation and cutting off inflammatory pathway via MG trapping. Thus, CE may be a potential natural product as an MG scavenger against diabetes‐related complications.